If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9-6x=-2
We move all terms to the left:
6x+9-6x-(-2)=0
We add all the numbers together, and all the variables
11!=0
There is no solution for this equation
| 9x+63=360 | | 6.5x-4.8(x-1)=7.1 | | 5x•13=5x•23 | | -7+n=-n-1 | | 30+x=180= | | x+8-4x-7= | | 6−8z=14 | | 30+x=90= | | (x+7)(x+2)=14 | | 2(7-3z)=2(10-5z) | | 1/2+y=20 | | 40+2x+4=180 | | 7(v–6)+17=50–8v. | | 8c×=3 | | 4(2x+5)=7(6=x) | | 4.3x-2.5(x-1)=6.8 | | 1/32^x=4^(2x-5) | | 14d=714 | | 15q=210 | | 4/2=n-10/n | | 15b+40=5b+120b= | | 2x^2/5-40x=0 | | 24=v/16 | | −4(y−3)=3(y+2) | | 3.4x-2.3(x-1)=5.9 | | -8x+24=36 | | -4x+(2x-3)^2=-6 | | 9x=-8x= | | 3.4-2.3(x-1)=5.9 | | 2x^-(7-x)x=11x | | 2x^2-(7-x)x=11x | | -2-3(4r-7)=103 |